The Students’ Perspectives toward the Activities and Materials Displayed in ELICA (English Listening Interactive Café) Web - Endah Ratnaningsih; Arum Nisma Wulanjani (Metathesis: Journal of English Language, Literature, and Teaching, 2019)
English Education students in Universitas Tidar have attended in the Intensive Listening Subject in the Academic Year of 2018/2019. This was a case-study which focused on the perspectives of the students toward the activities and materials displayed in ELICA website. There were 4 classes of Intensive Listening which were participated in this semester with 110 as the number of the students joined. A set of questionnaires and an interview were used in this research. From the result, it was found that most of the students agreed that the activities and the materials displayed in the ELICA can be used for making their listening skill improved.